Are there associations between submaximal and maximal aerobic power and International Ski Federation World Cup Ranking in elite alpine skiers? - Schobersberger, W.; Mairhofer, M.; Haslinger, S.; Koller, A.; Raschner, C.; Puntscher, S.; Blank, C. (International Journal of Sports Physiology and Performance, 2021)
Purpose: To analyze the predictive value of parameters of submaximal and maximal cardiopulmonary exercise performance on International Ski Federation (Fédération Internationale de Ski) World Cup ranking (FIS ranking) in elite Austrian Alpine skiers.